2020
DOI: 10.2147/cmar.s242425
|View full text |Cite
|
Sign up to set email alerts
|

<p>MALAT1 Promotes Cell Tumorigenicity Through Regulating miR-515-5p/EEF2 Axis in Non-Small Cell Lung Cancer</p>

Abstract: Background: Previous studies suggested long noncoding RNA metastasis associated with lung adenocarcinoma transcript 1 (lncRNA MALAT1) acted as a tumor promoter to promote cell carcinogenesis in non-small cell lung cancer (NSCLC). MALAT1 was found to exist in serum exosomes of several cancers. However, the role of exosomal-derived MALAT1 in NSCLC remains poorly understood. Materials and Methods: Exosomes were isolated using the ExoQuick precipitation kit. Western blot was used to detect the protein expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…In future studies, the effect of MALAT1 should be further examined using in vivo experiments. Rong et al ( 33 ) observed that MALAT1-knockdown repressed NSCLC tumorigenicity by inhibiting cell proliferation and invasion, and promoting apoptosis via regulating miR-515-5p/EEF2. Although the types of tumor cells investigated in the present study were not consistent with the aforementioned study, the current results confirmed those of the study by Rong et al ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future studies, the effect of MALAT1 should be further examined using in vivo experiments. Rong et al ( 33 ) observed that MALAT1-knockdown repressed NSCLC tumorigenicity by inhibiting cell proliferation and invasion, and promoting apoptosis via regulating miR-515-5p/EEF2. Although the types of tumor cells investigated in the present study were not consistent with the aforementioned study, the current results confirmed those of the study by Rong et al ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rong et al ( 33 ) observed that MALAT1-knockdown repressed NSCLC tumorigenicity by inhibiting cell proliferation and invasion, and promoting apoptosis via regulating miR-515-5p/EEF2. Although the types of tumor cells investigated in the present study were not consistent with the aforementioned study, the current results confirmed those of the study by Rong et al ( 33 ). The present study focused on thymic cancer, which is rarer in clinical practice, and the current results may therefore have a high clinical value and may provide a possible molecular-targeted therapy for patients with thymic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, eEF2 has increasingly been implicated in neurosynaptic plasticity (Verpelli et al ., 2010), NF-κB-associated innate immune response network (Bianco et al ., 2019), and tumor progression as an oncogene (Oji et al ., 2014; Sun et al ., 2015; Rong et al ., 2020). While the relevance of eEF2 to the cytoskeleton remains poorly elucidated, these discoveries may suggest its role in cytoskeletal regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 1, 2021. ; https://doi.org/10.1101/2021.06.01.446528 doi: bioRxiv preprint Rong et al, 2020). While the relevance of eEF2 to the cytoskeleton remains poorly elucidated, these discoveries may suggest its role in cytoskeletal regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Rong et al found that the levels of MALAT1 in serum exosomes were higher in patients with NSCLC, suggesting that exosome-derived MALAT1 may also reflect the biological changes of NSCLC cells (49). Zhang et al found that the expression of MALAT1 in serum exosomes of NSCLC patients was upregulated and that the level of exosomal MALAT1 was positively correlated with tumor stage and lymph node metastasis (67).…”
Section: Application Of Malat1 In Nsclcmentioning
confidence: 99%